Community dynamics and co-occurrence relationships of pelagic ciliates and their potential prey at a coastal and an offshore station in the ultra-oligotrophic Eastern Mediterranean Sea - Romano, Filomena; Pitta, Paraskevi; John, Uwe (Frontiers in Genetics, 2023)
Ciliates have been recognized as one of the major components of the microbial food web.Studying ciliate dynamics contributes to our understanding of the way the ecosystem functions, especially in ultra-oligotrophic waters, such as the Eastern Mediterranean Sea, where nutrients are scarce and therefore the microbial community is dominated by pico-and nano-sized organisms (picoeukaryotes, nanoflagellates), and ciliates are the main planktonic grazers. However, little is known about the community structure of heterotrophic and mixotrophic ciliates and how they are associated to their potential prey. In this study, we used 18S V4 rRNA gene metabarcoding to analyze ciliate communities. Samples were collected seasonally at two stations of the Eastern Mediterranean Sea (HCB: coastal, M3A: offshore) from the surface and deep chlorophyll maximum (DCM) layers. The ciliate community structure varied across depths in HCB and across seasons in M3A, showing that, although the two stations are quite close to each other, the ciliate dynamics differed between them. The network analysis showed that in both stations, mixotrophic oligotrichs were positively associated with diatoms and showed few negative associations with ASVs annotated as marine Stramenopiles (MAST). On the other hand, heterotrophic tintinnids showed negative relationships in both HCB and M3A stations, mostly with Ochrophyta and Chlorophyta. In conclusion, this study reports that mixotrophic and heterotrophic ciliates may have different ecological niches and that mixotrophic ciliates may be more selective compared to heterotrophic species regarding their prey. These findings the first glimbs into an understanding of the dynamics between heterotrophic and mixotrophic ciliates and their role in microbial assemblages and dynamics of ultra-oligotrophic environments.